A Comprehensive Review of Zavegepant as Abortive Treatment for Migraine - Nazir Noor; Alexis Angelette; Abby Lawson; Anjana Patel; Ivan Urits; Omar Viswanath; Cyrus Yazdi; Alan D. Kaye (Health Psychology Research)
Migraine headache is a widespread and complex neurobiological disorder that is characterized by unilateral headaches that are often accompanied by photophobia and phonophobia. Migraine is one of the leading chief complaints in the emergency department with negative impacts on quality of life and activities of daily living. The high number of emergency presentations also results in a significant economic burden. Its risk factors include family history, genetics, sex, race, socioeconomics, the existence of comorbid conditions, and level of education. Triggers include stress, light, noise, menstruation, weather, changes in sleep pattern, hunger, dehydration, dietary factors, odors, and alcohol. The International Headache Society has defined criteria for the diagnosis of migraine with and without aura. The pathophysiology of migraine headaches is multifactorial so there are a variety of treatment approaches. The current treatment approach includes abortive medications and prophylactic medications. Abortive medications include the first-line treatment of triptans, followed by ergot alkaloids, and calcitonin gene-related peptide (CGRP) receptor antagonists along with supplemental caffeine and antiemetics. Trigeminal afferents from the trigeminal ganglion innervate most cranial tissues and many areas of the head and face. These trigeminal afferents express certain biomarkers such as calcitonin gene-related peptide (CGRP), substance P, neurokinin A, and pituitary adenylate cyclase-activating polypeptide that are important to the pain and sensory aspect of migraines. In this comprehensive review, we discuss Zavegepant, a calcitonin gene-related peptide receptor antagonist, as a new abortive medication for migraine headaches.